2010
DOI: 10.1002/macp.201000375
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Meta‐Form Structure in the Stereocomplex of Poly(D‐lactic acid) with Low‐Molecular‐Weight Poly(L‐lactic acid)

Abstract: The crystalline structure and crystallization behavior of PLLA crystals in a 1:1 w/w mixture of low‐MW PLLA with high‐MW PDLA were analyzed using WAXD, DSC, and SAXS. Under cold crystallization, homopolymeric PLLA, appearing as a meta crystal, was discovered in the PDLA/LMW‐PLLA blend. The meta‐ and α′ crystal forms of PLLA were found to form on crystallization at a Tcc of 85–95 °C and the α crystal PLLA formed at 100 ≤ Tcc < 120 °C. The meta‐crystal PLLA may be incorporated in the stereocomplexed PDLA/LMW‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 47 publications
4
11
0
Order By: Relevance
“…Both P hc and P sc shift to low q with increasing T c , meaning the enhancement of long period of hc and sc crystallites (Table 3). Long periods of sc crystallites range 11−17 nm, which agree with the results reported by Li et al 57 and Woo et al 58 It is notable that, at the same T c , the long period of sc crystallites is much smaller than that of homocrystallites. Long diffusion path and large kinetic barrier of stereocomplexation may restrict the formation of thick crystalline lamellae.…”
Section: ■ Experimental Sectionsupporting
confidence: 91%
“…Both P hc and P sc shift to low q with increasing T c , meaning the enhancement of long period of hc and sc crystallites (Table 3). Long periods of sc crystallites range 11−17 nm, which agree with the results reported by Li et al 57 and Woo et al 58 It is notable that, at the same T c , the long period of sc crystallites is much smaller than that of homocrystallites. Long diffusion path and large kinetic barrier of stereocomplexation may restrict the formation of thick crystalline lamellae.…”
Section: ■ Experimental Sectionsupporting
confidence: 91%
“…In addition, the preorder state melted completely and recrystallized with the unmelted original crystals, which acted as nuclei, when T a was higher than 225 °C [Figure (b)]. We observed that the preorder state was different from the δ (or α′, disordered α) form of PLA . As reported in these studies, the δ form of PLA was attained upon certain crystalline conditions and characterized by in situ WAXD and IR spectroscopy; it transformed into the α form upon direct heating, and this was considered a solid‐to‐solid transition .…”
Section: Discussionsupporting
confidence: 51%
“…The exotherm was attributed to the cold crystallization of homocrystals. It was related to α ′ crystal formation [23]. An additional exotherm was observed on the non-reversing curve between approximately 105 °C and 165 °C.…”
Section: Resultsmentioning
confidence: 99%